Understanding Childfree: A Phenomenological Perspective and Islamic Law - Nur Sodiq; Muhammad Chairul Huda (Journal of Islamic Studies and Civilization, 2023)
Having children is one of the goals in marriage, but in reality, is that some followers of the childfreelife Instagram account are not. This research addresses the following questions: First, what are the motives and actions of childfree? Second, what is the ideal of Islamic law in the childfreelife.id account? This study is conducted from the perspective of phenomenology and maqashid of Islamic law. This research uses a qualitative descriptive method with a socio-legal approach. Data collection techniques through participation in being followers and in-depth telephone interviews. In order to obtain primary data, and literature studies to acquire secondary data. The findings of this study show the courage of followers to seek justification for childlessness, even though it goes against the purpose of marriage and social norms.